Enhancing Reading Comprehension through Collaborative Strategic Reading - Muhammad Lukman Syafii (Pascasarjana Universitas Negeri Makassar, 2022)
This study aims at improving learners’ reading comprehension through collaborative strategic reading. This study is implemented in the first semester of the accounting study program of Universitas Muhammadiyah Ponorogo. The investigator got two matters in the teaching and learning of learners in the first semester: (1) The learners’ attainment scores were poor in reading skills. (2) The English lecturer generally recited the story first and then he just requested the learners to go over after him. To overcome these problems, the researcher applied the classroom action research design. The subject of this research is class A consisting of 30 students. The researcher utilized some instruments such as an observation, checklist, field notes, and reading comprehension tests. The result shows that the students’ achievement score improved from 30% (9 students) of 30 students in the preliminary study to 53.3% (16 students) in Cycle 1 and then improved to 77% (23 students) in Cycle 2. From this, It can be concluded that the students could understand the texts comprehensively and they found a progressive enhancement in their attainment scores in reading comprehension.